Trening all' Odin Teatret Film II. Trening fisico = physical training - Odin Teatret Film ([Holstebro, Denmark] : Odin Teatret Film, 1972)
Odin Teatret's physical training, with a commentary by Eugene Barba, featuring the evolution from collectively learned skills to the actor's personalisation of the exercises.
Distributed in Australia by Contemorary Arts Media
DVD format
Italian dialogue, with English subtitles
Keywords: Odin teatret; Theater -- Denmark; Experimental theater